2006
DOI: 10.1073/pnas.0606924103
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia xenovorans LB400 harbors a multi-replicon, 9.73-Mbp genome shaped for versatility

Abstract: Burkholderia xenovorans LB400 (LB400), a well studied, effective polychlorinated biphenyl-degrader, has one of the two largest known bacterial genomes and is the first nonpathogenic Burkholderia isolate sequenced. From an evolutionary perspective, we find significant differences in functional specialization between the three replicons of LB400, as well as a more relaxed selective pressure for genes located on the two smaller vs. the largest replicon. High genomic plasticity, diversity, and specialization withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
280
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(295 citation statements)
references
References 66 publications
(67 reference statements)
12
280
0
3
Order By: Relevance
“…In Burkholderia, Chain et al (2006) also showed that the different replication units are evolving under independent evolutionary dynamics. Even though no significant fitness effect has been detected in S. meliloti strains characterized by atypical genome architectures (Guo et al, 2003), the organisation and the polymorphism of the S. medicae genome raise questions about the mechanisms leading to the differing gene content of its replicons and the possible adaptive nature of this organisation.…”
Section: Discussionmentioning
confidence: 99%
“…In Burkholderia, Chain et al (2006) also showed that the different replication units are evolving under independent evolutionary dynamics. Even though no significant fitness effect has been detected in S. meliloti strains characterized by atypical genome architectures (Guo et al, 2003), the organisation and the polymorphism of the S. medicae genome raise questions about the mechanisms leading to the differing gene content of its replicons and the possible adaptive nature of this organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of several bacterial genome sequences revealed the presence of more than one PHA synthase in many species. In strains of the genus Burkholderia, the presence of multiple PHA synthase genes is common, all sharing similar neighbouring genes (Chain et al, 2006;Holden et al, 2004;Nierman et al, 2004). In R. eutropha strain JMP222, a phaC2 gene has been identified (sequence available online http://www.jgi.doe.gov) that is neither a homologue of the phaC1 family of PHA synthase genes nor similar to phaC2 from strain H16.…”
Section: Correlation Between Transcriptomic and Proteomic Datamentioning
confidence: 99%
“…In agreement with the promoter distribution of the chr genes, the B. xenovorans LB400 genome encodes four rpoD genes (encoding s 70 ) and two rpoN genes (encoding s 54 ) as its main transcriptional factors (Chain et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…For example, the B. xenovorans LB400 9.7 Mb genome displays 17.6 % of redundant genes, a relatively large value when compared with other bacterial genomes, which average 7.6 % (±4.0 %); possession of multiple paralogues, as a result of gene duplication, has been related to the high level of metabolic versatility displayed by B. xenovorans LB400 (Chain et al, 2006). The largest number of redundant genes in B. xenovorans pertains to transport proteins (230 paralogues), including 180 efflux systems, which comprise 21 heavy metal efflux pumps (Chain et al, 2006). Among these transporters are the six homologues of the CHR superfamily: four proteins from the monodomain LCHR family and two protein pairs from the bidomain SCHR family (Díaz-Pérez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation